On Optical Dipole Moment and Radiative Recombination Lifetime of Excitons in WSe2. (27th September 2016) - Jin, Chenhao; Kim, Jonghwan; Wu, Kedi; Chen, Bin; Barnard, Edward S.; Suh, Joonki; Shi, Zhiwen; Drapcho, Steven G.; Wu, Junqiao; Schuck, Peter James; Tongay, Sefaattin; Wang, Feng
Abstract : Optical dipole moment is the key parameter of optical transitions, as it directly determines the strength of light–matter interaction such as intrinsic radiative lifetime. However, experimental determination of these fundamental properties of excitons in monolayer WSe2 is largely limited, because the commonly used measurement, such as (time‐resolved) photoluminescence, is inherently difficult to probe the intrinsic properties. For example, dark states below bright exciton can change the photoluminescence emission rate by orders of magnitude and gives an "effective" radiative lifetime distinctive from the intrinsic one. On the other hand, such "effective" radiative lifetime becomes important itself because it describes how dark states affect exciton dynamics. Unfortunately, the "effective" radiative lifetime in monolayer WSe2 is also not determined as it requires photoluminescence measurement with resonant excitation, which is technically difficult. These difficulties are overcome here to obtain both the "intrinsic" and "effective" radiative lifetime experimentally. A framework is developed to determine the dipole moment and "intrinsic" radiative lifetime of delocalized excitons in monolayer WSe2 from the absorption measurements. In addition, the "effective" radiative lifetime in WSe2 is obtained through time‐resolved photoluminescence and absolute quantum‐yield measurement at resonant excitation. These results provide helpful information for fundamental understanding of exciton light–matter interaction in WSe2 . Abstract : The dipole moment and "intrinsic" radiative lifetime of excitons in WSe2 are determined from absorption measurements. The "effective" radiative lifetime of excitons is also obtained using time‐resolved photoluminescence and absolute quantum yield measurements with resonant excitation. The framework developed provides helpful information to determine fundamental quantities of exciton light–matter interaction, and to understand the dynamics of delocalized excitons in solids.